Practice of Local Cultural Documentation of Dadung Awuk Art by Kancabudaya, Badan Pelestarian Nilai Budaya Yogyakarta: Praktik Dokumentasi Budaya Lokal Kesenian Dadung Awuk Oleh Kancabudaya Badan Pelestarian Nilai Budaya Yogyakarta - Hastuti, Aziza Tri; Fatmawati, Andriyana; Sayyidatul Aqma, Silvia; Oktavia, Devita (Tik Ilmeu : Jurnal Ilmu Perpustakaan dan Informasi, 2025)
Documentation is an effort made to preserve community culture. This research aims to determine the documentation process in Dadung Awuk art. To fulfill the required data, this research was conducted using qualitative methods through a case study approach technique. The data collection techniques used are observation, interviews and documentation. The data analysis techniques used are data analysis techniques in the form of data reduction, data display, and conclusion drawing. Meanwhile, to check the validity test using data triangulation techniques. The results of this research show that the Kancabudaya team has documented Dadung Awuk art through the process of recording and managing it. The results of the documentation process are in the form of articles, Instagram teasers and documentary videos with a duration of 20 minutes 12 seconds. The documentary video was uploaded to Kancabudaya YouTube account. Meanwhile, video collection has been done by storing them on CD-ROM and hard disk. CD-ROM and hard disk management is grouped according to code number and date of manufacture. So in this case the Kancabudaya team from the Badan Pelestarian Nilai Budaya is considered to have succeeded in documenting Dadung Awuk art using a process based on the theories that have been explained.